2012
DOI: 10.1155/2012/534384
|View full text |Cite
|
Sign up to set email alerts
|

Cigarette Smoke Extract Stimulates Rat Pulmonary Artery Smooth Muscle Cell Proliferation via PKC-PDGFB Signaling

Abstract: Accumulating evidence suggests a direct role for cigarette smoke in pulmonary vascular remodeling, which contributes to the development of pulmonary hypertension. However, the molecular mechanisms underlying this process remain poorly understood. Platelet-derived growth factor (PDGF) is a potential mitogen and chemoattractant implicated in several biological processes, including cell survival, proliferation, and migration. In this study, we investigated the effect of cigarette smoke extract (CSE) on cell proli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 35 publications
1
10
0
Order By: Relevance
“…Studies also evidenced that CSE induced apoptosis of human airway SMCs [ 43 , 44 ], human pulmonary endothelial cells [ 10 ], and vascular endothelial cells [ 45 ]. In controversy, Xing and his colleagues [ 46 ] reported that stimulation of rat pulmonary artery SMCs with CSE significantly increased cell proliferation and promoted cell cycle progression. Promotions of cell proliferations stimulated by CSE were also observed on bovine tracheal SMCs [ 47 ] and human aortic SMCs [ 3 ].…”
Section: Discussionmentioning
confidence: 99%
“…Studies also evidenced that CSE induced apoptosis of human airway SMCs [ 43 , 44 ], human pulmonary endothelial cells [ 10 ], and vascular endothelial cells [ 45 ]. In controversy, Xing and his colleagues [ 46 ] reported that stimulation of rat pulmonary artery SMCs with CSE significantly increased cell proliferation and promoted cell cycle progression. Promotions of cell proliferations stimulated by CSE were also observed on bovine tracheal SMCs [ 47 ] and human aortic SMCs [ 3 ].…”
Section: Discussionmentioning
confidence: 99%
“…Proliferation of smooth muscle cells seems to be mediated via activation of the platelet-derived growth factor-protein kinase C signaling cascade. 68,69 Furthermore, polycyclic aromatic hydrocarbons (part of the hydrophobic fraction of cigarette smoke) were shown to activate aryl hydrocarbon receptor, which induces iNOS, leading finally to intimal thickening. 70 Likewise, polycyclic aromatic hydrocarbon-activated aryl hydrocarbon receptors can induce the transcription of receptors for chemokines and adhesion molecule receptors for leukocytes, thus amplifying inflammatory signals on the vascular endothelium.…”
Section: Arterioscler Thromb Vasc Biol March 2014mentioning
confidence: 99%
“…PDGF acts as a mitogen and chemoattractant for VSMCs and induces transition of the mature contractile VSMCs into a proliferative and secretory phenotype. Further, cigarette smoke induced PDGF- protein kinase C signalling has been shown to induce VSMC proliferation [79]. PDGF, via PDGF receptor beta (PDGFRβ), also induces STAT-1 signalling pathway that leads to disease progression.…”
Section: Modulation Of Vsmc Dynamics and Atherosclerosismentioning
confidence: 99%